2019
DOI: 10.1021/acs.iecr.9b05350
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydroformylation in a Continuous Flow Microreactor System

Abstract: A microreactor system consisting of a honeycomb microreactor and microtubing was proposed to enhance the Rh-biphephos catalyzed hydroformylation of 1-hexene. The effects of various reaction parameters were investigated. The isomerization, which turned the terminal olefins into isoolefins, occurred first in the beginning of the reaction. The increasing residence time, gas-to-liquid ratio, pressure, temperature, and biphephos/Rh ratio favored the catalytic cycle of hydroformylation, resulting in the increasing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 61 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Recently, Zhang et al developed a nature-inspired microreactor which is capable of increasing the gas–liquid mixing [ 563 ]. The reactor consists of an honeycombed microchannel reactor in which the channel cappilaries and branches assist with breaking the gas slugs up, enhancing the contact area in the mixture.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, Zhang et al developed a nature-inspired microreactor which is capable of increasing the gas–liquid mixing [ 563 ]. The reactor consists of an honeycombed microchannel reactor in which the channel cappilaries and branches assist with breaking the gas slugs up, enhancing the contact area in the mixture.…”
Section: Reviewmentioning
confidence: 99%
“…In order to overcome these hurdles to meet industrial production demands, researchers turned to investigate hydroformylation in microreactors due to a high surface-to-volume ratio, efficient heat and mass transfer, as well as precise control and enhanced safety in the process. Vorholt and coworkers have improved reactor designs, enhancing the stirring structure to speed up the reaction rate in kettle reactors and using jet loop and microbubble reactors to improve mass transfer in gas–liquid–liquid systems. , Wiese and coworkers optimized the surface-to-volume ratio using a packed tube reactor with Sulzer SMV internals for hydroformylation in water-soluble rhodium–phosphine multiphase, achieving a 10-fold performance increase, suggesting its potential as a replacement for traditional stirred vessels. However, the complexity of the equipment and substantial investment costs should be taken into consideration for industrial production …”
Section: Introductionmentioning
confidence: 99%
“…For example, in ref , the highest known hydroformylation TOF of 75,000 h –1 was reached in an MF unit. The authors of ref showed that under similar conditions, a flow system provided more effective hydroformylation compared to a classical batch reactor. In addition, the application of classical Rh/phosphine complexes and a Rh complex with water-soluble ligand TPPTS (tris(3-sulfophenyl)phosphine trisodium salt) for intensified biphasic HF using the MF system was recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%